A prospective study to evaluate changes in macular thickness after uncomplicated cataract surgery using optical coherence tomography in diabetic patients - Jamaiyar, Anshu; Kumar, Sunil; Kiran, Neha; Mahato, Rohit Kumar; Anand, Mousmi (International Journal of Research in Medical Sciences, 2023)
Background: The objective of this study is to evaluate the alterations in macular thickness subsequent to cataract surgery in individuals diagnosed with diabetes, utilising optical coherence tomography (OCT) as the imaging modality. Methods: In this prospective study, a cohort of 150 patients was divided into three equal groups based on their diabetic status and presence of retinopathy. Group 1 consisted of nondiabetic patients, Group 2 consisted of diabetic patients without retinopathy, and group 3 consisted of patients with diabetic retinopathy. All patients underwent cataract surgery using manual small incision cataract surgery (m-SICS) technique. A comprehensive ophthalmological assessment was conducted prior to the surgical procedure. The subjects were monitored on the first day following the surgical procedure, and at 2, 6 and 12 weeks after the operation. During each appointment, a comprehensive ophthalmic assessment and OCT of the macula were conducted. Results: There was a notable augmentation in foveal thickness at the 6-week mark among individuals diagnosed with diabetic retinopathy, in contrast to those without retinopathy and the control group. In the study, it was observed that 26% of individuals diagnosed with diabetes experienced the occurrence of macular edoema, whereas only 4% of the control group exhibited the same condition. Conclusions: The postoperative alteration in macular thickness and visual outcomes is contingent upon the individual’s diabetic condition, duration of diabetes, and severity of retinopathy. A positive correlation was also observed between the alteration in macular thickness and the levels of HbA1C in individuals diagnosed with diabetes.